Islamic Architecture vs Islamicate Architecture : A Critical Review of Concepts, Identity, and Spatial Manifestation - Novalinda Novalinda; Cut Nuraini; Nangkula Utaberta (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The terminological debate between “Islamic architecture” and “Islamicate architecture” has become a central concern in studies of architecture rooted in Islamic values. Although often used interchangeably, the two terms carry different theoretical and contextual nuances. This study aims to explore the conceptual similarities and differences between Islamic architecture and Islamicate architecture through an interpretative qualitative approach by examining both classical and contemporary literature, as well as architectural spaces that represent the two terms. The analysis reveals that Islamic architecture refers more to the historical products of classical Islamic civilization, while Islamicate architecture is a contemporary approach that seeks to embed Islamic values into the design process, regardless of traditional architectural forms. This study emphasizes the importance of terminological clarity in developing an architectural identity grounded in values and spirituality. The implication is that conceptual approaches to Islamic and Islamicate architecture can enrich contemporary architectural discourse in an inclusive and contextual manner.